2003
DOI: 10.1038/nm929
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PDGFR as a receptor for AAV-5 transduction

Abstract: Understanding the process of vector transduction has important implications for the application and optimal use of a vector system for human gene therapy. Recent studies with vectors based on adeno-associated virus type 5 (AAV-5) have shown utility of this vector system in the lung, central nervous system, muscle and eye. To understand the natural tropism of this virus and to identify proteins necessary for AAV-5 transduction, we characterized 43 cell lines as permissive or nonpermissive for AAV-5 transduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
209
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(219 citation statements)
references
References 37 publications
(54 reference statements)
8
209
0
2
Order By: Relevance
“…Immunolabeling experiments revealed that the GFP-expressing cells were GFAP-positive astrocytes, regardless of the serotype used for transduction (AAV1, 2,7,8,9). At 1-2 weeks post-transduction, both neurons and astrocytes showed robust GFP fluorescence after transduction by AAV1, 2, 7, 8 or 9, indicating that the early expression in astrocytes and later expression in neurons is principally a result of hCMV promoter usage in each cell type (Fig.…”
Section: Time Course Of Expressionmentioning
confidence: 90%
“…Immunolabeling experiments revealed that the GFP-expressing cells were GFAP-positive astrocytes, regardless of the serotype used for transduction (AAV1, 2,7,8,9). At 1-2 weeks post-transduction, both neurons and astrocytes showed robust GFP fluorescence after transduction by AAV1, 2, 7, 8 or 9, indicating that the early expression in astrocytes and later expression in neurons is principally a result of hCMV promoter usage in each cell type (Fig.…”
Section: Time Course Of Expressionmentioning
confidence: 90%
“…rIL-10 was also administered subcutaneously in an acute model using intratracheal lipopolysaccharide (LPS) challenge in CF mice, resulting in a significant decrease of polymorphonuclear neutrophils and TNF-a that correlated with decreased nuclear factor-kB activity and increased IkBa. 21 This study also addressed current barriers to sufficient gene expression by AAV gene transfer through employing an AAV5 pseudotyped vector, which binds to apically expressed receptors (2,3-linked sialic acid and the platelet-derived growth factor) [38][39][40] and a potent promoter (Cb), previously demonstrated to be highly effective in the murine lungs. 41 Despite high levels of IL-10 protein expression in the lungs of mice receiving AAV5.Cb-mIL10, blood levels of proinflammatory cytokines and IL-10 from mice receiving AAV5.Cb-mIL10 were not significantly different from those measured in PBS-treated mice.…”
Section: Aav5cb-mil10 Mediates Il-10 Protein Expression In the Alveolimentioning
confidence: 99%
“…[31][32][33] These vectors have a proven safety profile and the ability to elicit a minimal inflammatory response in comparison with other gene transfer agents. [34][35][36][37] To increase lung-specific delivery and promote high levels of gene expression, we used an AAV5 pseudotyped vector for efficient airway transduction [38][39][40] and the CMV (Cytomegalovirus)/chicken-b-actin hybrid (Cb) promoter, a promoter with robust activity in the murine lung. 41 Using these elements, we hypothesized that AAV-based gene transfer of IL-10 would result in high levels of lung-specific IL-10 expression, ameliorating the excessive response in the lung without systemic immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…40 Similarly, platelet-derived growth factor receptor (PDGFR) has been considered the coreceptor for AAV5 and is also required for efficient infection with this serotype. 54 However, PDGFR itself is a sialo-glycoprotein containing both N-and O-linked oligosaccharide chains with sialic acid. 55,56 This suggests that PDGFR may be capable of acting alone as a receptor for AAV5.…”
Section: Aav Attachment Receptors and Coreceptorsmentioning
confidence: 99%